2019
DOI: 10.1111/jep.13169
|View full text |Cite
|
Sign up to set email alerts
|

Vocal fold medialization—A 5‐year series of single surgeon consecutive medialization with review of literature

Abstract: Introduction: ENT UK released guidelines in 2010 detailing the requisite structure for the creation of a laryngeal intervention clinic. The senior author's practice is the only one regionally that offers this service, and our objective was to review this to determine whether vocal cord medialization injections were showing an improvement in quality of voice for patients. Materials and methods:Patients were reviewed in a specialist voice clinic prior to being offered vocal cord injection under local anaesthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Patients receiving a repeated procedure saw a signifi cantly smaller improvement in VHI-10 than those where it was the primary treatment (mean reduction: 9.8 vs 15.5, p = .018). Analysis of MPT found a signifi cant correlation between the quantity of injection material used and the degree of improvement observed (rho = 0.355, p = .004) (7).…”
Section: Discussionmentioning
confidence: 96%
“…Patients receiving a repeated procedure saw a signifi cantly smaller improvement in VHI-10 than those where it was the primary treatment (mean reduction: 9.8 vs 15.5, p = .018). Analysis of MPT found a signifi cant correlation between the quantity of injection material used and the degree of improvement observed (rho = 0.355, p = .004) (7).…”
Section: Discussionmentioning
confidence: 96%
“…With regard to vocal cord medialisation the most popular options are injection laryngoplasty (IL) and type I thyroplasty 6 (Using Sialastic or Titanium) or a combination of both techniques. With regard to injection laryngoplasty some studies have also shown a corelation between and quality and quantity of material used with improvement of maximum phonation time (MPT) 7 .…”
Section: Discussionmentioning
confidence: 99%